Larval and early juvenile development of Lithodes santolla (Molina, 1782) (Decapoda: Anomura: Lithodidae) reared at different temperatures in the laboratory - Anger, Klaus (2004)
While the diversity of decapod crustaceans, in general, tends to decline in cold-temperate and subpolar waters as compared to warm-temperate and tropical regions, the number of lithodid crab species remains stable or increases with increasing latitude (e.g. Arntz et al., 1994, Arntz et al., 1997, Klages et al., 1995, Gorny, 1999, Zaklan, 2002). Recent experimental studies suggested that this deviating distributional pattern of the Lithodidae among the reptant decapods is due to special adaptations of their early life-history stages to conditions of cold and food-limitation in high latitudes, namely tolerance of low temperatures and lecithotrophic (i.e. food-independent) larval development Anger et al., 2003, Calcagno et al., 2003, Calcagno et al., 2004, Kattner et al., 2003, Lovrich et al., 2003, Thatje et al., 2003. Since lithodids have generally a large body size and a high market value as “king crabs” or “stone crabs”, several species are commercially fished, representing economically valuable fishery resources in subpolar regions Dawson, 1989, Lovrich, 1997, Sundet and Hjelset, 2002. The southern king crab, Lithodes santolla Molina, is one of those species, although its commercially exploited populations have dramatically declined in recent years, due to heavy overfishing in preceding times (Lovrich and Vinuesa, 1999). L. santolla is distributed in a large area along the southeastern Pacific and southwestern Atlantic coasts, stretching from the subantarctic waters of the Beagle Channel (Tierra del Fuego, southernmost parts of Argentina and Chile; 55°S) to the cold-temperate region around the island of Chiloé (southern-central Chile; 42°S; see Retamal, 1981, Boschi et al., 1992, Gorny, 1999) and the deeper parts (ca. 700 m depth) of the continental slope off Uruguay (Vinuesa, 1991). Its larval development comprises three zoeal stages and a megalopa which were morphologically described by Campodonico (1971) and McLaughlin et al. (2001). Recent biochemical and elemental analyses of fed and unfed larvae showed that all four larval stages are completely nonfeeding, which was interpreted as an adaptation to early development under conditions of low water temperature and low or short planktonic productivity during the austral winter Calcagno et al., 2003, Calcagno et al., 2004, Kattner et al., 2003, Lovrich et al., 2003. In the present study, we reared larval and early juvenile southern king crabs at various constant temperatures in the laboratory (1) to identify the tolerated or preferred thermal range for successful postembryonic development and growth, and (2) to quantify the effect of variation in temperature on the rate of moulting and development through the early life-history stages.